2003
DOI: 10.1136/gut.52.10.1479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a protein and energy dense n-3 fatty acid enriched oral supplement on loss of weight and lean tissue in cancer cachexia: a randomised double blind trial

Abstract: Aim: N-3 fatty acids, especially eicosapentaenoic acid (EPA), may possess anticachectic properties. This trial compared a protein and energy dense supplement enriched with n-3 fatty acids and antioxidants (experimental: E) with an isocaloric isonitrogenous control supplement (C) for their effects on weight, lean body mass (LBM), dietary intake, and quality of life in cachectic patients with advanced pancreatic cancer. Methods: A total of 200 patients (95 E; 105 C) were randomised to consume two cans/day of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
377
2
24

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 516 publications
(411 citation statements)
references
References 24 publications
8
377
2
24
Order By: Relevance
“…To illustrate, in patient in whom compliance in the ONS was low, it may be that ONS that are not enriched with EPA could be used, and instead, EPA supplementation given via oral capsule. Previous intervention studies have also demonstrated that compliance with ONS34 and exercise35 can be challenging, and there is an obvious risk that the control group may adopt the intervention. However, contamination in the control arm was limited in the present study, and this clearly bodes well for future trial designs adopting this approach.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, in patient in whom compliance in the ONS was low, it may be that ONS that are not enriched with EPA could be used, and instead, EPA supplementation given via oral capsule. Previous intervention studies have also demonstrated that compliance with ONS34 and exercise35 can be challenging, and there is an obvious risk that the control group may adopt the intervention. However, contamination in the control arm was limited in the present study, and this clearly bodes well for future trial designs adopting this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Among the problems associated with the translation of DR into clinical applications is that chronic DR delays but does not stop the progression of the disease (Mukherjee et al, 2004;Bonorden et al, 2009;Shelton et al, 2010), and that this delay will occur for only a subset of malignancies (Kalaany and Sabatini, 2009). Although weight loss and cachexia in the early stages of cancer progression are not as common as thought (Tisdale, 2002;Fearon et al, 2003;Fox et al, 2009), the B15% loss of body mass index caused by a moderate (20%) calorie restriction (Racette et al, 2006) would prevent its use in the great majority of cancer treatment scenarios. In addition, the effect of long-term restriction in delaying wound healing and impairing immune function Kristan, 2008;Reed et al, 1996) may impose a significant risk to cancer patients receiving chemotherapy, surgery or immunity-based treatments (Kim and Demetri, 1996).…”
Section: Dr and Cancer Treatmentmentioning
confidence: 99%
“…However, despite what appeared to be a promising approach, the results from the phase 2 trial were equivocal (41) .…”
Section: Cancermentioning
confidence: 99%